Validity and repeatability of the Vicorder apparatus : a comparison with the SphygmoCor device - Hickson, Stacey S; Butlin, Mark; Broad, Jeremy; Avolio, Alberto P; Wilkinson, Ian B; McEniery, Carmel M (Hypertension research, 2009)
Aortic stiffness, an independent predictor of cardiovascular risk and all-cause mortality, can be estimated non-invasively by measuring carotid to femoral (aortic) pulse wave velocity (aPWV). The Vicorder device has been developed to measure aPWV with little operator training in a non-intrusive manner. The aim of this study was to assess the repeatability of aPWV measured with the Vicorder device and to compare aPWV values with those obtained using the SphygmoCor system. Vicorder and SphygmoCor aPWV was assessed in 122 subjects (53±18 years, 46 male) using both the manufacturers' and a standardized approach. Vicorder aPWV measurement proved to be highly repeatable (within-subject coefficient of variation 2.8%). Transit time differed significantly between the two devices (mean difference 22±9 ms, P <0.001), independent of the different algorithms used to calculate transit time. However, aPWV was similar between the two devices (mean difference 0.31±1.54 m s −1 , P <0.001) though with an inherent bias toward lower Vicorder aPWV values at high values of SphygmoCor aPWV. Bias was reduced by subtracting the additional femoral artery segment measured by the Vicorder device, also bringing the measure of transit time in closer agreement to SphygmoCor values (mean difference 5±9 ms, P <0.001). Transit time values significantly differed between the two devices and the Vicorder device reported lower aPWV values at higher SphygmoCor values of aPWV. This difference in transit time and inherent bias was reduced when adjustment for the additional femoral artery segment measured by the Vicorder device was made.